2011
DOI: 10.1038/onc.2011.392
|View full text |Cite
|
Sign up to set email alerts
|

Loss of breast epithelial marker hCLCA2 promotes epithelial-to-mesenchymal transition and indicates higher risk of metastasis

Abstract: Transition between epithelial and mesenchymal states is a feature of both normal development and tumor progression. We report that expression of chloride channel accessory protein hCLCA2 is a characteristic of epithelial differentiation in the immortalized MCF10A and HMLE models, while induction of EMT by cell dilution, TGFbeta, or mesenchymal transcription factors sharply reduces hCLCA2 levels. Attenuation of hCLCA2 expression by lentiviral shRNA caused cell overgrowth and focus formation, enhanced migration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
92
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(101 citation statements)
references
References 55 publications
7
92
0
Order By: Relevance
“…22 Thus, hCLCA2 and its murine orthologue have been proposed as tumour suppressor genes in breast cancer. 23, 24 However, other investigators have demonstrated an upregulation of hCLCA2 in triple-negative breast cancer patients with a poor prognosis, 25 perhaps suggesting breast cancer subtype specific roles, and exemplifying the need for further characterization of this poorly understood protein family.…”
mentioning
confidence: 99%
“…22 Thus, hCLCA2 and its murine orthologue have been proposed as tumour suppressor genes in breast cancer. 23, 24 However, other investigators have demonstrated an upregulation of hCLCA2 in triple-negative breast cancer patients with a poor prognosis, 25 perhaps suggesting breast cancer subtype specific roles, and exemplifying the need for further characterization of this poorly understood protein family.…”
mentioning
confidence: 99%
“…The chloride channel calcium-activated (CLCA) 3 proteins are a complex family targeted for a role in cancer (1,2) and inflammatory diseases (3) but are poorly understood in terms of molecular structure and function. The original annotation of this family as calcium-activated chloride channels (CaCCs) was based on the observation that overexpression of several different CLCA paralogues from various species all induced chloride current in response to cytosolic calcium flux (4,5).…”
mentioning
confidence: 99%
“…Similarly, reduced levels of the related isoform CLCA4 is a feature of subpopulations of cells from the HMLE cell line that are enriched in mesenchymal markers and a consequence of TGFβ-induced EMT (Yu et al 2013). Consistent with the loss of CLCA2 and CLCA4 in the mesenchymal phenotype, low levels of CLCA2 and CLCA4 appear likely to be associated with an increased incidence of metastasis (as assessed through metastasis or relapse free survival) using specific cohorts of breast cancer patients (Walia et al 2012, Yu et al 2013. In addition to their remodelling as a consequence of EMT, CLCA2 and CLCA4 have also been implicated in the regulation of the transition of breast cancer cells towards a more mesenchymal state.…”
Section: Chloride Channels and Emt In Cancer Cellsmentioning
confidence: 73%
“…MCF-7). Indeed, expression of the EMT Shiwarski et al (2014) transcription factor Snail supresses CLCA2 protein in the human breast cell line MCF10A, and CLCA2 levels are reduced in subpopulations of cells from the human mammary epithelial (HMLE) cell line that are enriched in mesenchymal markers (Walia et al 2012). Moreover, CLCA2 levels are reduced during EMT induced by TGFβ (Yu et al 2013).…”
Section: Chloride Channels and Emt In Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation